Understanding the sources, function, and irreplaceable role of cobamides in organohalide-respiring bacteria - Lu, Yongfeng; Lu, Fancheng; Zhang, Jian; Tang, Qianwei; Yang, Dan; Liu, Yaqing (Frontiers in Microbiology, 2024)
Halogenated organic compounds are persistent pollutants that pose a serious threat to human health and the safety of ecosystems. Cobamides are essential cofactors for reductive dehalogenases (RDase) in organohalide-respiring bacteria (OHRB), which catalyze the dehalogenation process. This review systematically summarizes the impact of cobamides on organohalide respiration. The catalytic processes of cobamide in dehalogenation processes are also discussed. Additionally, we examine OHRB that cannot synthesize cobamide and must obtain it from the environment through salvage pathway, the co-culture with cobamides producer form is more beneficial and possible. This review aims to help readers better understand the importance and function of cobamides in reductive dehalogenation. The presented information can aid in the development of bioremediation strategies.